Britain, Sanctions, and the Oligarchs: An Analysis of Crisis Communication and Image Restoration in the Ukraine Conflict - Yonarisman Muhammad Akbar; Dina Fadiyah; Sapto Setyo Nugroho (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2026)
Russia's invasion of Ukraine triggered a series of economic sanctions from the UK targeting the Russian government and influential oligarchs with significant assets abroad, particularly in the UK. As a global financial center, London faced a major challenge in balancing sanctions enforcement with maintaining domestic economic stability. This situation created a complex communications crisis, where the UK government had to explain sanctions policy, manage public and international perceptions, and maintain domestic support. Russian billionaires, on the other hand, sought to defend their image and access through media campaigns and legal remedies. The research method used is qualitative research with a literature study design. The data collection technique uses secondary data from reference sources such as legal products, research articles, and journals collected from Google Scholar, Portal Garuda, and news portals. The literature study technique uses a traditional review also explores the communication dynamics that took place between the UK government, the Russian oligarchs and various other stakeholders. The focus is on how transparency, consistency and stakeholder engagement can help manage a communications crisis in this complex geopolitical context. The findings of this study provide insights into effective communication strategies in the face of stressful and challenging international situations. Keywords: Communication crisis, Sanctions, Russia-Ukraine military operation, London, International diplomacy, international relations, Sanction policy.